2014
DOI: 10.1155/2014/924030
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Association betweenCCR5rs333 Polymorphism and Childhood Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is a malignant disorder that originates from one single hematopoietic precursor committed to B- or T-cell lineage. Ordinarily, these cells express CCR5 chemokine receptor, which directs the immune response to a cellular pattern and is involved in cancer pathobiology. The genetic rs333 polymorphism of CCR5 (Δ32), results in a diminished receptor expression, thus leading to impaired cell trafficking. The objective of the present study was to investigate the effect of CCR5 chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The migration of regulatory immune cells to tumor sites can create an immunosuppressor environment proper for cancer development. Also, cancer cells can subvert the anti-tumor action of chemokine-ligand interactions (187)(188)(189)(190)(191). Of note, CD4+ T cells are important modulators of the immune response, acting as drivers for the action of effector cells.…”
Section: Ccr5d32 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The migration of regulatory immune cells to tumor sites can create an immunosuppressor environment proper for cancer development. Also, cancer cells can subvert the anti-tumor action of chemokine-ligand interactions (187)(188)(189)(190)(191). Of note, CD4+ T cells are important modulators of the immune response, acting as drivers for the action of effector cells.…”
Section: Ccr5d32 In Cancermentioning
confidence: 99%
“…In this sense, Vieira-Filho et al (191) found an association between the presence of the CCR5D32 allele and susceptibility to neuroblastoma (191). Lastly, Oliveira et al (187) investigated the role of the CCR5D32 variant in acute lymphoblastic leukemia, but no association was found between the variant and the disease development (187). In conclusion, the CCR5 has varied influences in different types of cancer.…”
Section: Ccr5d32 In Cancermentioning
confidence: 99%
“…As a member of the CC chemokine receptor group, chemokine C-C motif receptor 5 (CCR5) can regulate the trafficking and effector functions of memory/effector T cells, macrophages, immature dendritic cells and natural killer cells [ 14 ]. This receptor binds to the chemokines MIP-1α (CCL3), MIP-1β (CCL4), and RANTES (CCL5), and exerts its functions through G protein [ 15 ]. In addition, CCR5 also plays a pivotal role in cancer progression via recruiting immune cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%